1992
DOI: 10.1029/91jd02531
|View full text |Cite
|
Sign up to set email alerts
|

Micrometeorological measurements of CH4 and CO2 exchange between the atmosphere and subarctic tundra

Abstract: Exchanges of methane and carbon dioxide between the atmosphere and the Arctic tundra were measured continuously near Bethel, Alaska (61ø05.41'N, 162ø00.92'W), for 5 weeks during July and August 1988. Fluxes were obtained directly using eddy correlation at 12-m altitude, and concentrations were measured sequentially at eight altitudes between 0 and 12 m. A prototype differential infrared absorption methane instrument based on a Zeeman-split HeNe laser was used for determination of methane and a flame ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
1
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 43 publications
11
65
1
4
Order By: Relevance
“…The scale and dynamics of growing-season methane emissions from tundra settings have been documented mostly through flux measurements made with low time resolution using manual chambers 5,6,10 together with some at higher time resolution taken only during the growing season 7,11,12 . Here we report a data set that extends hourly CH 4 flux measurements from a high Arctic setting into the frozen season.…”
Section: Lettersmentioning
confidence: 99%
“…The scale and dynamics of growing-season methane emissions from tundra settings have been documented mostly through flux measurements made with low time resolution using manual chambers 5,6,10 together with some at higher time resolution taken only during the growing season 7,11,12 . Here we report a data set that extends hourly CH 4 flux measurements from a high Arctic setting into the frozen season.…”
Section: Lettersmentioning
confidence: 99%
“…Fan et al, 1992;Sturtevant et al, 2012;Zona et al, 2016), providing insight into factors controlling CH 4 emissions at the scale of ∼ 1 m to ∼ 1 km. These studies have revealed that CH 4 emissions are spatially inhomogeneous at those scales and are highly dependent on local conditions such as soil moisture, temperature, elevation, and soil carbon.…”
mentioning
confidence: 99%
“…мере определяющая измеренную величину общего потока, например, 90% этого потока ("…footprint, i. e., the area contributing by percentage, e. g., 90% of the total flux"). Подробное рассмотрение теории футпринта и конкретные модели для него см., например, в [36][37][38][39][40][41], причем в работе [36] даны ссылки еще на 22 конкретные модели футпринта.…”
Section: область влияния (футпринт)unclassified